2010
DOI: 10.1097/jsm.0b013e3181c967cd
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Injury Among Adolescent Soccer Players: A Comparative Study of Artificial and Natural Grass Turfs

Abstract: Adolescent players routinely training on AT for prolonged periods should be carefully monitored, even on AT conforming to new standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 17 publications
2
42
1
Order By: Relevance
“…Modern, artificial turfs, compared with natural grass, have the benefit of not being affected by weather conditions (eg, temperature and rain) 29 ; however, young soccer players training on artificial turf often report pain. 2,28 This finding is not corroborated by recent epidemiological studies showing that the use of a third-generation artificial turf is not associated with a higher risk of muscular injuries than natural grass. 11,23,28 Indeed, pressure sensitivity decreases (measured as an increase in pressure pain threshold [PPT]) among soccer players accustomed to playing on artificial turf compared with natural grass.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…Modern, artificial turfs, compared with natural grass, have the benefit of not being affected by weather conditions (eg, temperature and rain) 29 ; however, young soccer players training on artificial turf often report pain. 2,28 This finding is not corroborated by recent epidemiological studies showing that the use of a third-generation artificial turf is not associated with a higher risk of muscular injuries than natural grass. 11,23,28 Indeed, pressure sensitivity decreases (measured as an increase in pressure pain threshold [PPT]) among soccer players accustomed to playing on artificial turf compared with natural grass.…”
contrasting
confidence: 53%
“…12 Complaints about the low back are common among young soccer players training on artificial turf. 2,28 Thus, the use of SAIs may help prevent lumbar pain among soccer players practicing on artificial turf. All in all, the findings in this study suggest that the nociceptive system was less sensitized after using SAIs for 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Studies comparing injury rates on third-generation AT and NG at youth [4][5][6] and collegiate levels 7,8 have not revealed statistically significant differences in general.…”
Section: Introductionmentioning
confidence: 99%
“…Previous injury surveillance studies in male and female elite, l,2,3 male and female intercollegiate, 4,5 and male and female youth level, 6,7,8 have found no overall differences in acute injury rates between natural grass (NG) and AT. However, one study found a decreased overall injury rate on AT in female intercollegiate football, 9 but this study used different injury and exposure definitions compared with previous studies which make comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%